Board Leadership Structure and Earning Quality: A Study from the Malaysian Banking Sector - Joanne Shaza, Janang; Nurshafarrina, Binti Abdul Rani; Kit Yeng, Sin; Farah Dipah, Khalid (International Journal of Academic Research in Accounting, Finance and Management Sciences, 2022)
The purpose of this study is to examine the relationship between board leadership structure and earning quality of banking sectors in Malaysia. This study purposely focuses on four sectors of board leadership structure which is board size, board independent non-executive director, board gender diversity and Chief Executive Officer (CEO) tenure. Data that is used in this study is 10 banking sectors in Malaysia that are publicly listed in Bursa Malaysia. As for the period, the data cover from the year 2016 to 2019. In order to find the value of earning quality, this study uses The Modified Jones Model by Dechow, Sloan and Sweeney (1995) since many previous studies have stated that The Modified Jones Model are the best model to measure earning quality. Based on the analysis, board size and board diversity show positive and insignificant association with earning quality while board independent and Chief Executive Officer (CEO) tenure shows negative and insignificant association with earning quality.